Wasnt asking for an answer, just if the steps were correct so far.
You told me to post a couple more on here to make sure I had gotten this...
This one is going to prove more difficult for me.
f(x) = the 4th root of (2x+1/1-3x)....the whole fraction under the 4th root.
u(x) = the 4th root of u or u^(-1/4)
u'(x) = -1/4u^(-5/4)
v(x) = [2x+1/1-3x]
v'(x) = (1-3x)(2) - (2x+1)(-3)/(1-3x)^2
v'(x) = (2-6x) - (-6x-3)/(1-3x)^2
v'(x) = -1/(1-3x)^2
If that is correct, I will move on with
u(x) * v'(x) - v'(x) * u(x)/u(x)^2